MOG-IgG in NMO and related disorders: a multicenter study of 50 patients. Part 3: Brainstem involvement - frequency, presentation and outcome. Issue 1 (December 2016) - Jarius, Sven; Kleiter, Ingo; Ruprecht, Klemens; Asgari, Nasrin; Pitarokoili, Kalliopi; Borisow, Nadja; Hümmert, Martin; Trebst, Corinna; Pache, Florence; Winkelmann, Alexander; Beume, Lena-Alexandra; Ringelstein, Marius; et al.
Abstract Background Myelin oligodendrocyte glycoprotein antibodies (MOG-IgG) are present in a subset of aquaporin-4 (AQP4)-IgG-negative patients with optic neuritis (ON) and/or myelitis. Little is known so far about brainstem involvement in MOG-IgG-positive patients. Objective To investigate the frequency, clinical and paraclinical features, course, outcome, and prognostic implications of brainstem involvement in MOG-IgG-positive ON and/or myelitis. Methods Retrospective case study. Results Among 50 patients with MOG-IgG-positive ON and/or myelitis, 15 (30 %) with a history of brainstem encephalitis were identified. All were negative for AQP4-IgG. Symptoms included respiratory insufficiency, intractable nausea and vomiting (INV), dysarthria, dysphagia, impaired cough reflex, oculomotor nerve palsy and diplopia, nystagmus, internuclear ophthalmoplegia (INO), facial nerve paresis, trigeminal hypesthesia/dysesthesia, vertigo, hearing loss, balance difficulties, and gait and limb ataxia; brainstem involvement was asymptomatic in three cases. Brainstem inflammation was already present at or very shortly after disease onset in 7/15 (47 %) patients. 16/21 (76.2 %) brainstem attacks were accompanied by acute myelitis and/or ON. Lesions were located in the pons (11/13), medulla oblongata (8/14), mesencephalon (cerebral peduncles; 2/14), and cerebellar peduncles (5/14), were adjacent to the fourth ventricle in 2/12, and periaqueductal in 1/12; some had concomitant diencephalic (2/13) or cerebellar lesions (1/14). MRI or laboratory signs of blood-brain barrier damage were present in 5/12. Cerebrospinal fluid pleocytosis was found in 11/14 cases, with neutrophils in 7/11 (3-34 % of all CSF white blood cells), and oligoclonal bands in 4/14. Attacks were preceded by acute infection or vaccination in 5/15 (33.3 %). A history of teratoma was noted in one case. The disease followed a relapsing course in 13/15 (87 %); the brainstem was involved more than once in 6. Immunosuppression was not always effective in preventing relapses. Interferon-beta was followed by new attacks in two patients. While one patient died from central hypoventilation, partial or complete recovery was achieved in the remainder following treatment with high-dose steroids and/or plasma exchange. Brainstem involvement was associated with a more aggressive general disease course (higher relapse rate, more myelitis attacks, more frequently supratentorial brain lesions, worse EDSS at last follow-up). Conclusions Brainstem involvement is present in around one third of MOG-IgG-positive patients with ON and/or myelitis. Clinical manifestations are diverse and may include symptoms typically seen in AQP4-IgG-positive neuromyelitis optica, such as INV and respiratory insufficiency, or in multiple sclerosis, such as INO. As MOG-IgG-positive brainstem encephalitis may take a serious or even fatal course, particular attention should be paid to signs or symptoms of additional brainstem involvement in patients presenting with MOG-IgG-positive ON and/or myelitis.